The Open Door : being Reforms suggested in the Report of the Enquiry on behalf of the Extension of Co-operation to the Poor, made by Women's Co-operative Guild - Women's Co-operative Guild
A paper for joint district conferences, held under the auspices of district associations and district committees of the Women's Co-operative Guild. Autumn, 1902.